2023
DOI: 10.3390/mti7020016
|View full text |Cite
|
Sign up to set email alerts
|

Ranking Crossing Scenario Complexity for eHMIs Testing: A Virtual Reality Study

Abstract: External human–machine interfaces (eHMIs) have the potential to benefit AV–pedestrian interactions. The majority of studies investigating eHMIs have used relatively simple traffic environments, i.e., a single pedestrian crossing in front of a single eHMI on a one-lane straight road. While this approach has proved to be efficient in providing an initial understanding of how pedestrians respond to eHMIs, it over-simplifies interactions which will be substantially more complex in real-life circumstances. A proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 113 publications
2
6
0
Order By: Relevance
“…Our interpretation is that when the far-away participant experienced the second block (i.e., two-pedestrian scenarios) after the first block (single-pedestrian scenarios), the sudden appearance of another person in the environment distracted and caught their attention, leading to longer decision time. Studies suggest that distracted pedestrians tend to initiate late road crossing [7], this is further confirmed by the longer gazing time toward another pedestrian. This finding is in line with [38], which similarly observed that participants farther from the AV chose narrower time margins to enter the road.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Our interpretation is that when the far-away participant experienced the second block (i.e., two-pedestrian scenarios) after the first block (single-pedestrian scenarios), the sudden appearance of another person in the environment distracted and caught their attention, leading to longer decision time. Studies suggest that distracted pedestrians tend to initiate late road crossing [7], this is further confirmed by the longer gazing time toward another pedestrian. This finding is in line with [38], which similarly observed that participants farther from the AV chose narrower time margins to enter the road.…”
Section: Discussionmentioning
confidence: 81%
“…The questionnaire included seven parts, namely (1) participant's information, (2) the face validity questionnaire, (3) the Simulator Sickness Questionnaire, (4) the Presence Questionnaire, (5) the Trust in AVs questionnaire, (6) the Perceived behavioral control and risk questionnaire, and (7) the System Usability Scale questionnaire. The personal information part included participants' characteristics such as gender, age, achieved highest education level, familiarity with the Marineterrein area, familiarity with computer gaming, familiarity with VR, familiarity with the concept of AVs, and experience regarding interaction with AVs.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature is replete with examples of confusing eHMI messages, such as the text GO (Eisma et al, 2021), arrows (Kunst et al, 2022;Zang et al, in press), and a red lamp (Bazilinskyy et al, 2020) being misunderstood regarding whether the message represents an instruction for the pedestrian or a representation of the AV's intent. Also, some light-based eHMIs have been misinterpreted as sensors instead of communication devices (Bazilinskyy et al, 2019;Fratini et al, 2021;Shutko et al, 2018).…”
Section: Argument 3 Against Ehmis: Ehmis Elicit Negative Effectsmentioning
confidence: 99%